2023
DOI: 10.3389/fimmu.2023.1257834
|View full text |Cite
|
Sign up to set email alerts
|

A hub gene signature as a therapeutic target and biomarker for sepsis and geriatric sepsis-induced ARDS concomitant with COVID-19 infection

Guojun Qian,
Hongwei Fang,
Anning Chen
et al.

Abstract: BackgroundCOVID-19 and sepsis represent formidable public health challenges, characterized by incompletely elucidated molecular mechanisms. Elucidating the interplay between COVID-19 and sepsis, particularly in geriatric patients suffering from sepsis-induced acute respiratory distress syndrome (ARDS), is of paramount importance for identifying potential therapeutic interventions to mitigate hospitalization and mortality risks.MethodsWe employed bioinformatics and systems biology approaches to identify hub gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…They have potential clinical utility as a biomarker in early diagnosis or prognosis of DCI and may be targets for therapeutic intervention due to their influential role in gene regulation pathways. Similar utility has been studied in a variety of pathologies such as glioblastoma [ 27 ], sepsis [ 28 ], colorectal cancer [ 29 ], and others [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…They have potential clinical utility as a biomarker in early diagnosis or prognosis of DCI and may be targets for therapeutic intervention due to their influential role in gene regulation pathways. Similar utility has been studied in a variety of pathologies such as glioblastoma [ 27 ], sepsis [ 28 ], colorectal cancer [ 29 ], and others [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that KLRB1 expression is downregulated in SLE ( 51 53 ), which is also consistent with the results of this paper. Apart from SLE, aberrant KLRB1 expression has been correlated with other autoimmune diseases and inflammatory responses, including rheumatoid arthritis (RA) ( 54 , 55 ), multiple sclerosis (MS) ( 56 ), and sepsis ( 57 ). Nevertheless, the expression of KLRB1 is not entirely consistent in these immunoinflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the expression of KLRB1 is not entirely consistent in these immunoinflammatory diseases. KLRB1 expression is up-regulated in early RA ( 54 ) and MS ( 56 ) and down-regulated in advanced RA ( 55 ) and sepsis ( 57 ). The exact mechanism remains unclear, but KLRB1 may develop into a biological marker specific to autoimmune diseases in the future.…”
Section: Discussionmentioning
confidence: 99%